2016
DOI: 10.1111/rda.12885
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, proliferation and characterization of endometrial canine stem cells

Abstract: In the last decade, progenitor cells isolated from dissociated endometrial tissue have been the subject of many studies in several animal species. Recently, endometrial cells showing characteristics of mesenchymal stem cells (MSC) have been demonstrated in human, pig and cow uterine tissue samples. The aim of this study was the isolation and characterization of stromal cells from the endometrium of healthy bitches, a tissue that after elective surgery is routinely discarded. Multipotent stromal cells could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Infrapatellar fat pad‐derived dMSCs though carry comparable proliferation potential to that of the synovium but the chondrogenesis may be better in case of Sy‐MSCs (Sasaki et al, ). Between dEn‐MSCs and dAD‐MSCs, former cells carry lower replicative potential as compared with latter (De Cesaris et al, ). dBM‐MSCs and dLi‐MSCs though carry similar proliferation potential but differ in their differentiation potential.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Infrapatellar fat pad‐derived dMSCs though carry comparable proliferation potential to that of the synovium but the chondrogenesis may be better in case of Sy‐MSCs (Sasaki et al, ). Between dEn‐MSCs and dAD‐MSCs, former cells carry lower replicative potential as compared with latter (De Cesaris et al, ). dBM‐MSCs and dLi‐MSCs though carry similar proliferation potential but differ in their differentiation potential.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Moreover, eMSCs could generate endometrial stroma in xenograft assays ( Masuda et al, 2010 ). eMSCs have been harvested and characterized from humans ( Cheng et al, 2017 ; Queckborner et al, 2020 ), pigs ( Miernik & Karasinski, 2012 ), heifers ( Calle et al, 2019 ; de Moraes et al, 2016 ), horses ( Cabezas et al, 2018 ), dogs ( De Cesaris et al, 2017 ; Sahoo et al, 2017 ) and sheep ( Ghobadi et al, 2018 ). This type of cells showed similar properties to bone marrow MSCs and may provide an available source for cell-based therapies due to their strong regenerative capacity ( Gargett et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The multipotent stem cells (MSCs) were first isolated and characterized from bone marrow [ 5 ] and later on from various tissues such as umbilical cord blood [ 6 ], adipose tissue [ 7 ], amniotic fluid [ 8 ], amniotic membrane [ 9 ], and peripheral blood [ 10 ]. The existence of endometrial mesenchymal stem cell (En-MSCs) population in different species has been demonstrated by different groups in heifer [ 11 ], human [ 12 ], murine [ 13 ], ovine [ 14 ], equine [ 15 ], and canine [ 16 ].…”
Section: Introductionmentioning
confidence: 99%